Egg deposition and weight loss of seeds by pulse beetle, Callosobruchus chinensis L. on different genotypes of pulses (Bangladesh Journal of Agricultural Research, 2019)
Lentil Lens culinarisMedik., mungbeanVignaradiata L. R. Wilczek, chickpea Cicer arietinum L. and blackgramVigna mungo L. Hepper of different genotypes were tested against pulse beetle, Callosobruchuschinensis L. in the laboratory of the Department of Entomology, Bangladesh Agricultural University (BAU), Mymensingh to evaluate the number of eggs deposition and percent weight loss of seeds. Maximum number of eggs (73.1) was oviposited on chickpea and minimum (19.5) was found on blackgram. The highest (19.9%) weight loss in seed was noted in chickpea and the lowest (7.6%) was recorded in blackgram. On the basis of weight loss of seed, blackgram and mungbean exhibited as tolerant genotype, lentil with moderately susceptible and chickpea as susceptible. Genotypes ML-22 of lentil, MC-21 of mungbean, Hyprosola of chickpea and MAK–1-79 of blackgram were found tolerant as compared to other tested genotypes considering the reduced number of egg deposition and lowest loss of seed weight. Evidently, the percent weight loss was marked as positive correlation with number of eggs deposition in all the genotypes and the regression line resulted in increasing the number of eggs laid with the increase in percent weight loss.Bangladesh J. Agril. Res. 44(3): 513-524, September 2019